ANALISIS PENGARUH NON PERFORMING FINANCING (NPF), CAPITAL ADEQUACY RATIO (CAR), FINANCING TO DEPOSIT RATIO (FDR), DAN BOPO TERHADAP PROFITABILITAS (STUDI KASUS PADA PT. BANK VICTORIA SYARIAH PERIODE 2011-2016) - Wahyu Dwi Yulihapsari; Dien Noviany Rahmatika; Jaka Waskito (Multiplier: Jurnal Magister Manajemen, 2017)
This study was conducted to examine the effect of variable Non Performing Financing (NPF), Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR) and ROA to profitability PT. Bank Victoria Syariah as measured by Return on Assets (ROA). Data used in the study was obtained from the Quarterly Financial Report 2011-2016 period issued by PT. Bank Victoria Syariah. The total sample of 21 with the technique of multiple regression analysis and hypothesis testing using t-test and F test with a significance level of 5%, which preceded the classical assumption. The results showed the dependent variable profitability (ROA) of 94.7% can be explained by variations in four independent variables (NPF, CAR, FDR and ROA) .In partial NPF and ROA significant negative effect on ROA, CAR significant positive effect on ROA, and FDR was not significant positive effect on ROA. Simultaneously NPF, CAR, FDR and BOPO effect on ROA. Keywords : Non Performing Financing (NPF) , Capital Adequacy Ratio (CAR) , Financing to Deposit Ratio (FDR) , ROA and Return on Assets (ROA)